Cerebral Augmentation Effect Induced by External Counterpulsation Is Not Related to Impaired Dynamic Cerebral Autoregulation in Ischemic Stroke - Xiong, Li; Chen, Xiangyan; Liu, Jia; Wong, Lawrence Ka Sing; Leung, Thomas W. (Frontiers in Neurology, 2022)
Background and Purpose Dynamic cerebral autoregulation is impaired after ischemic stroke. External counterpulsation (ECP) augments cerebral blood flow of ischemic stroke patients by elevation of blood pressure (BP). We aimed to investigate if cerebral augmentation effects during ECP was associated with impaired dynamic cerebral autoregulation in patients after acute ischemic stroke. Methods Forty patients with unilateral ischemic stroke and large artery atherosclerosis in the anterior circulation territory within 7 days from symptom onset and eighteen healthy controls were recruited. We monitored changes in mean flow velocity over both middle cerebral arteries (MCA) by transcranial Doppler (TCD) before, during and immediately after ECP. Cerebral augmentation index was MCA mean flow velocity increase in percentage during ECP compared with baseline to evaluate the augmentation effects of ECP. Spontaneous arterial BP and cerebral blood flow velocity in both bilateral MCAs were recorded using a servo-controlled plethysmograph and TCD, respectively. Transfer function analysis was used to derive the autoregulatory parameters, including phase difference (PD) and gain. Results The cerebral augmentation index in stroke patients was significantly higher on both the ipsilateral and contralateral sides than that in controls, while the PD in stroke patients were significantly lower on both sides than those in controls (all P < 0.05). The cerebral augmentation index did not correlate with PD and gain on either the ipsilateral or contralateral side of stroke patients or in controls (all P > 0.05). The cerebral augmentation index of stroke patients was significantly related to mean BP change on the ipsilateral side (R2 = 0.108, P = 0.038). Conclusion The degree of ECP induced cerebral augmentation effects as measured by the cerebral augmentation index did not correlate with the magnitude of impaired dynamic cerebral autoregulation.